A wearable circular polarized antenna - Mohamed Ali, Abdiladif (2022)
Recently, wearable electronic applications have arising in the commercial market. There has been growing use of textile antennas for wearable electronic and body centric applications such as health care, GPS and fire fighterlpersonal communications. The use of circularly polarized antennas presents an attractive solution to achieve this polarization match which allows for more flexibility in the angle between transmitting and receiving antennas the new generation of textile has the capability to conduct electricity and at the same time as wearable. Microstrip patch antennas represent one family of[compact antennas that offer a conformal nature and the capability of ready integration with communication system’s printed circuitry. In this project, a circular polarized (CP) textile antenna is designed and simulated at 1.5 GHz. circular polarization (CP) textile antenna is designed for Global Positioning System (GPS) application. The truncated rectangular patch antenna is having a full ground plane from Shieldiet and felt as a substrate. The proposed antenna operates at 1.5 GHz with a good bandwidth from 1.5 to 1.52 GHz. The optimized chamfer has been made at two edges of a rectangular patch in order to produce a Circular Polarization with a good axial ratio (AR) bandwidth of 1.5 GHz to 1.52 GHz, morever I made bending different way such concave, covex and degree last compare result in reflection coeffient. This manuscript also presents the analytical performances ofoCP textile antenna under bending condition that suitable for the on-body antenna applications.